Analysis of the Implementation of Project Based Learning Learning Models in Improving Students' Digital Literacy Through Digital Content Creation Training at SMAN 3 Bengkulu Tengah - Risdianto, Eko; Apiri, Enton (CV Media Inti Teknologi, 2022)
This study aims to analyze the implementation of the project based learning model in improving students' digital literacy through training in digital content creation. This type of research is survey research. The study was conducted in October 2022. The research sample was 27 students from SMAN 3 Bengkulu Tengah. Sampling is done by purposive sampling technique. The research instrument used was a closed questionnaire consisting of 18 positive statementswhich was developed in the form of a modified Likert Scale with 4 answer choices, namely strongly agree, agree, disagree and strongly disagree.The data analysis technique used is descriptive statistical analysis. The results showed that the implementation of the project-based learning model through digital content creation training activities carried out at SMAN 3 Bengkulu Tengah was able to add insight and skills, especially from practitioners of digital content creation.